Stable knockout of lanthionine synthase C-like protein-1 (LanCL1) from HeLa cells indicates a role for LanCL1 in redox regulation of deubiquitinating enzymes - Downey, Aaron; Olcott, Melissa; Spector, Daniel; Bird, Kayla; Ter Doest, Amanda; Pierce, Zachary; Quach, Evan; Sparks, Sawyer; Super, Christa; Naifeh, Jefferey; Powers, Andrea; White, Matthew; et al. (Free radical biology & medicine, 2020)
Lanthionine synthase C-like protein-1 (LanCL1) is a glutathione (GSH)-binding protein of uncertain function, widely expressed in mammalian cells. Recent data suggests that LanCL1 has glutathione S-transferase (GST)-like activity, while other reports claim that LanCL1 suppresses mitogen-activated kinase (MAPK) phosphorylation. In the present study, recombinant human LanCL1 had less than 10% the specific activity of GST. When CRISPR-Cas9 was used to stably ablate LanCL1 from HeLa cells, the resulting line was sensitized to H2O2 toxicity. [GSH], [GSSG], [GSH]/[GSSG] and GST activity were unaltered by LanCL1 knockout but glutathione reductase and glutathione peroxidase activities were significantly elevated. LanCL1-KO cells did not differ in basal or H2O2–induced p38-MAPK, ERK p42/p44 or JNK phosphorylation; however, MAPK-targeted transcription factor regulators c-Jun and IκBα were significantly decreased. Because c-Jun and IκBα levels are ubiquitin regulated, experiments addressed the hypothesis that LanCL1 affects ubiquitination dynamics. In the presence of the 26S proteasome inhibitor bortezomib, ubiquitinated proteins accumulated faster in LanCL1-KO cells, suggesting that LanCL1 positively regulates deubiquitination. The activity of ubiquitin C-terminal hydrolase (UCH), a major deubiquitinase (DUB) subclass, was significantly decreased in LanCL1-KO cells while protein levels of A20/TNFAIP3, USP9X and USP10 DUBs were significantly reduced. UCH activity in HeLa cell lysates was lost upon treatment with H2O2 and significantly recovered by addition of recombinant LanCL1 plus GSH. Taken together these data suggest that LanCL1 likely does not act as a GST-like enzyme in vivo, but rather modulates ubiquitin-dependent cell signaling pathways through positive regulation of redox-sensitive DUBs. [Display omitted] •Deubiquitinases (DUBs) are proteases that remove ubiquitin from proteins.•Some cysteinyl DUBs are subject to reversible oxidative inactivation.•LanCL1 is a glutathione-binding protein of uncertain function.•LanCL1 acts with glutathione to positively regulate deubiquitinase activity.•LanCL1 is a novel redox mediator for protein ubiquitination dynamics.